Role of grey scale ultrasound and Colour Doppler findings to differentiate ectopic pregnancy from corpus luteum cyst of pregnancy - Kaur, Navkiran; Kaur, Irwinjit; Bansal, Aman; Kaur, Parneet (International Journal of Medical Research and Review, 2019)
Introduction: Ectopic pregnancy and corpus luteum cyst are two most common differential diagnosis in a patient with UPT positive and no sonographic evidence of intrauterine pregnancy. Aim: To diagnose ectopic pregnancy and to differentiate ectopic pregnancy from corpus luteum cyst of pregnancy on the basis of grey scale ultrasound and colour Doppler findings. Material and Methods: This was a hospital based prospective study carried out on a study group of 40 patients with UPT positive and clinical features suggestive of ectopic pregnancy over a period of two years.Grey scale ultrasound and colour Doppler parameters were studied. Results: Out of 40 patients,30 were diagnosed with ectopic pregnancy and 10 with corpus luteum cyst. Ectopic pregnancies had thicker walls as compared to corpus luteum cysts. Most of the ectopic pregnancies had hyperechoic walls as compared to ovaries (80%) and endometrium (60%). Free fluid with echoes was seen in the pelvis in 70% ectopic pregnancies whereas most of the corpus luteum cysts (80%) had no free fluid. Most of the corpus luteum cysts (70%) had clear internal echotexture whereas ectopic pregnancies were mostly lacy or solid.Yolk sac was seen exclusively in ectopic pregnancy (30%). RI <0.4 and RI >0.7 was found to be highly specific for diagnosing ectopic pregnancy. Conclusion: Wall thickness of the mass, echogenicity of the wall as compared to ovaryand endometrium, internal echotexture of the cystic mass, presence of yolk sac and presence of free fluid with echoes are significant ultrasound parameters which help to differentiate between the two. RI <0.4 and RI >0.7 was found to be highly specific for diagnosing ectopic pregnancy.